A Practical Approach to Android Mobile Application Security - Sakir TASDEMIR; Ahmet CALISKAN (International Journal of Applied Methods in Electronics and Computers, 2018)
In parallel to rapid developments in computer technology, the number of mobile applications developed for the devices also increases. Mobile applications make life easier, but also bring some risks. These applications may create some weaknesses due to mistakes in the app development or use phase. In this study, a sample security test was performed for mobile application security awareness. This paper related to phising attacks to Android mobile users and data storage security on Android device. The sample mobile application has been decompiled. The malicious code was injected into the sample app. After the code was injected into the sample banking application developed, the user interface was modified. In addition, when the application is open, the user's credit card information is requested. After the user fills information, the credit card information is sent to a different phone number (attacker’s phone number) through an SMS. The mobile user is at risk of stealing sensitive information. This study also shows that the data stored in the device can be accessed through the Android Debug Bridge (ADB) shell commands. As a result, this paper shows that the application developer should be more careful during the development phase and the device user should be more careful during the use phase.